Traumatic Brain Injury Alters Cerebral Concentrations and Redox States of Coenzymes Q9 and Q10 in the Rat - Giacomo Lazzarino; Renata Mangione; Miriam Wissam Saab; Barbara Tavazzi; Alessandra Pittalà; Stefano Signoretti; Valentina Di Pietro; Giuseppe Lazzarino; Angela Maria Amorini (Antioxidants, 2023)
To date, there is no information on the effect of TBI on the changes in brain CoQ levels and possible variations in its redox state. In this study, we induced graded TBIs (mild TBI, mTBI and severe TBI, sTBI) in male rats, using the weight-drop closed-head impact acceleration model of trauma. At 7 days post-injury, CoQ9, CoQ10 and α-tocopherol were measured by HPLC in brain extracts of the injured rats, as well as in those of a group of control sham-operated rats. In the controls, about the 69% of total CoQ was in the form of CoQ9 and the oxidized/reduced ratios of CoQ9 and CoQ10 were, respectively, 1.05 ± 0.07 and 1.42 ± 0.17. No significant changes in these values were observed in rats experiencing mTBI. Conversely, in the brains of sTBI-injured animals, an increase in reduced and a decrease in oxidized CoQ9 produced an oxidized/reduced ratio of 0.81 ± 0.1 (p < 0.001 compared with both controls and mTBI). A concomitant decrease in both reduced and oxidized CoQ10 generated a corresponding oxidized/reduced ratio of 1.38 ± 0.23 (p < 0.001 compared with both controls and mTBI). An overall decrease in the concentration of the total CoQ pool was also found in sTBI-injured rats (p < 0.001 compared with both controls and mTBI). Concerning α-tocopherol, whilst no differences compared with the controls were found in mTBI animals, a significant decrease was observed in rats experiencing sTBI (p < 0.01 compared with both controls and mTBI). Besides suggesting potentially different functions and intracellular distributions of CoQ9 and CoQ10 in rat brain mitochondria, these results demonstrate, for the first time to the best of knowledge, that sTBI alters the levels and redox states of CoQ9 and CoQ10, thus adding a new explanation to the mitochondrial impairment affecting ETC, OXPHOS, energy supply and antioxidant defenses following sTBI.